Clinical presentation and treatment of orthopaedic implant‐associated infection. (August 2014) - Zimmerli, W.
Abstract Orthopaedic implants are highly susceptible to infection. The aims of treatment of infection associated with internal fixation devices are fracture consolidation and prevention of chronic osteomyelitis. Complete biofilm eradication is not the primary goal, as remaining adherent microorganisms can be removed with the device after fracture consolidation. By contrast, in periprosthetic joint infection (PJI), biofilm elimination is required. Surgical treatment of PJI includes debridement with retention, one‐ or two‐stage exchange and removal without reimplantation. In addition, prolonged antibiotic treatment, preferably with an agent that is effective against biofilm bacteria, is required. Rifampicin is an example of an antibiotic with these properties against staphylococci. However, to avoid the emergence of resistance, rifampicin must always be combined with another antimicrobial agent. With this novel treatment approach, orthopaedic implant‐associated infection is likely to be eradicated in up to 80–90% of patients. Because most antibiotics have a limited effect against biofilm infections, novel prophylactic and therapeutic options are needed. Surface coating with antimicrobial peptides that reduce bacterial attachment and biofilm formation can potentially prevent implant‐associated infection. In addition, quorum‐sensing inhibitors are a novel therapeutic option against biofilm infections.